1991
DOI: 10.1128/jvi.65.7.3633-3640.1991
|View full text |Cite
|
Sign up to set email alerts
|

Common mechanism of retrovirus activation and transduction of c-mil and c-Rmil in chicken neuroretina cells infected with Rous-associated virus type 1

Abstract: We previously described the isolation of the IC10 retrovirus which transduced the v-Rmil oncogene, a new member of the millraf gene family. This virus was generated during serial passaging of Rous-associated virus type 1 (RAV-1) in chicken embryo neuroretina (NR) cells and was selected for its ability to induce proliferation of these nondividing cells. IC10 was isolated after six passages of culture supernatants but was not detected in proliferating NR cells during early virus passages. In this study, we molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Therefore, all B‐Raf isoforms contain this peptide and are recognized by the IS11 (as an antiexon 11 serum). The IS11 serum was previously used in several studies to immunoprecipitate B‐Raf proteins from neuroretina infected cells (Felder et al . 1991), Cos1‐transfected cells (Eychène et al .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, all B‐Raf isoforms contain this peptide and are recognized by the IS11 (as an antiexon 11 serum). The IS11 serum was previously used in several studies to immunoprecipitate B‐Raf proteins from neuroretina infected cells (Felder et al . 1991), Cos1‐transfected cells (Eychène et al .…”
Section: Resultsmentioning
confidence: 99%
“…This experimental cell system also proved useful in establishing a precursor-product relationship between viruses generated successively during milIRmil transduction. Specifically, we showed that late virus forms were generated by further recombination involving sequence homologies between oncogenes and the RAV-1 gag gene (5,6). Therefore, the proposed model may account for the generation of the vast majority of transforming viruses which contain a 5' junction between gag and oncogene exonic sequences (22).…”
Section: L2 Cef Nr2mentioning
confidence: 99%
“…We reported that serial in vitro passaging of Rous-associated virus type 1 , an avian retrovirus that does not carry an oncogene, in chicken embryo neuroretina (NR) cells results in reproducible transduction of the catalytic domain of two related serine/ threonine protein kinases (15,16), c-mil/c-raf (13,14,18) and c-Rmil/B-raf (10). By comparing the genetic organization of several viruses isolated after few or multiple passages of culture supernatants on NR cells, we were able to establish a precursor-product relationship between viruses generated at different stages of transduction (5,6). We showed that the 5' end of early-passage viruses was generated by a splice mechanism between the donor site of RAV-1 leader sequences and acceptor sites of the activated exons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homologous recombination in retroviruses, also proposed to occur during reverse transcription (15,19,20,40), occurs at a very high frequency, with markers as close as 1 kb apart segregating independently, suggesting that RT jumps frequently between copackaged genomic RNA (29). In the case of nonhomologous recombination, it is not known whether certain sequences or short stretches of homology promote RT jumps, since examples of recombination breakpoints at areas of either patchy homology (11,23,45) or no homology (1,26,38,43) are found in naturally occurring transforming viruses. Several systems have been described to study nonhomologous recombination during reverse transcription.…”
mentioning
confidence: 99%